When Fulfillment is Not Enough: Early Childhood Teacher Occupational Burnout and Turnover Intentions from a Job Demands and Resources Perspective. Issue 7 (2nd October 2020) - Schaack, Diana D.; Le, Vi-Nhuan; Stedron, Jennifer
ABSTRACT: Research Findings : This study examined the job demands and job resources of a sample of 273 early childhood teachers in Colorado. The study explored the relationships among their job demands and resources, occupational burnout, and turnover intentions using a two-level mediated model. Study findings suggest that teachers' emotional exhaustion and depersonalization from the work is a function of lack of job control, lack of collegial relationships within the program, and children's behaviors that they perceived to be challenging. However, teachers also reported being more fulfilled with their work when they worked in programs in which there was a shared vision and that allowed for greater job control. Additionally, teachers who earned lower wages, held a postsecondary degree, reported greater emotional exhaustion, and who expressed less of a shared vision with their organization were more likely to indicate intentions to leave their job. Higher levels of collegiality were indirectly related to lower turnover intentions via lower levels of emotional exhaustion among teachers. Policy or Practice : Study findings can be used to inform leadership development, teacher professional development, and workforce compensation policy to foster greater organizational health, to improve teacher well-being, and to promote teacher retention.